Aquaculture : farming aquatic animals and plants - Lucas, John S. , 1940- (Wiley-Blackwell, 2012)
This new edition covers all major aspects of the culture offish, shellfish and algae in freshwater and marineenvironments. * International in scope makes it suitable for both northern andsouthern waters. * Written by around 30 of the world's well-known andwell-respected experts